Cell In Vitro Testing with Soil Invertebrates—Challenges and Opportunities toward Modeling the Effect of Nanomaterials: A Surface-Modified CuO Case Study - Maria J. Ribeiro; Mónica J.B. Amorim; Janeck J. Scott-Fordsmand (Nanomaterials, 2019)
Soil invertebrates have been widely used in ecotoxicology studies for decades, although their use as in vitro models, albeit promising, has not been pursued as much. The immune cells of earthworms (coelomocytes) and the coelomic fluid can be used, and are a highly relevant in vitro system. Although it has been tested before, to cover the testing of nanomaterials (NMs), several challenges should be considered. NMs characteristics (dispersibility, agglomeration, etc.) can interfere with the common in vitro methodologies, not only during exposure, but also during the measurements. Here, we have assessed the effect of a CuO NMs case study using surface-modified particles, functionalized for safe-by-design strategies with ascorbate, citrate, polyethylenimine, and polyvinylpyrrolidinone, plus the pristine CuO NMs and copper chloride (CuCl2) for comparison. Eisenia fetida’s coelomocytes were exposed for 24 h via the coelomic fluid. Changes in cell viability were evaluated using flow cytometry. All materials affected the cells in a dose-related manner, where CuCl2 was the most toxic followed by the citrate-coated CuO NM. There was a strong correlation between NM characteristics, e.g., the hydrodynamic size, and the EC50 (50% Effect Concentrations) values. This screening further confirms the potential for the usage of the standard earthworm model as an in vitro standard. Further detailed in vitro studies are needed using other NMs aiming toward their implementation and standardization. Additional cell endpoints can also be assessed, making it a high content tool for mechanistic understanding.